To start or not to start: Outcome and ability expectations in the decision to start a new venture - Townsend, David M.; Busenitz, Lowell W.; Arthurs, Jonathan D. (Journal of Business Venturing, 2010)
This study seeks to better understand why some individuals decide to start new businesses and others do not, particularly in light of high base rates of failure. In addressing the question of “Why do some individuals choose to start new ventures?” a common perspective is that potential entrepreneurs with high levels of confidence in potential outcomes are likely to start new ventures. Alternatively, it also may be that firm creation decisions are based largely on individual expectations of one's ability. Hypotheses examining these perspectives are tested using a sample of 316 nascent entrepreneurs with the start-up decision tracked longitudinally. The results indicate that confidence in one's ability to perform tasks relevant to entrepreneurship is a robust predictor of start-up while outcome expectancies appear to play a marginal role. Theoretical and practical implications stemming from these results are discussed.